Muslim Women in the Face of Feminism: Bint Ash-Shati’s Concept of Equality and Emancipation to the Rescue - SURAJU, Saheed Badmus; OMOTOSHO, Haleemah Olajumoke (Online Journal of Research in Islamic Studies, 2024)
In recent times, Feminism is said to be the movement to end women’s oppression. Muslim feminism emerged as a challenge to patriarchy in Muslim societies in support of Western feminism. The discourse on Islamic feminism has generated an ideology that many young Muslim women have misconstrued because Islam is seen as the main factor in the subjugation of women in the world. Thus, this paper examined the complex relationship between Islam and Western feminism theories and their implications on contemporary Muslim women. The methodologies adopted are analytical; which aided in analyzing misconceptions of Islam and feminism and the view of Bint Al-Shāṭi on feminist interpretations, historical which was used in accounting for the biography of Bint Al-Shāṭi and the phenomenological method which was used to relate the discussion to contemporary society. The findings of the research revealed that there is a primary difference between a secular Muslim feminist and an Islamic feminist. It also revealed that Muslim women have been lost in the hands of erroneous interpretations by Muslim feminists while seeking to westernize gender equality, freedom, and liberation using a feminist perspective in re-reading the Qur’ān. The paper concluded that gender equity, women’s emancipation and freedom have been an integral part of Islamic history. It therefore recommended that Muslim women should rediscover the true meaning of Islamic teachings on gender equity, gender justice, gender sexuality, women’s dress, and patriarchy, among others that have been lost at the hands of erroneous interpretation. It also recommended that Muslim women should do away with the spirit of the inferiority complex that has been proposed by the Western feminism theory.